Creative and Critical Thinking, and Ways to Achieve It - de Gastyne, Michèle (Journal of Interdisciplinary Studies in Education, 2020)
This paper discusses creative and critical thinking across wide cultural and historical frameworks. It begins with an exploration of Socratic Dialectics in multiple contexts, highlighting the need for innovative views and investigative practices using Art and Culture. A major objective of this project is to use the Arts for finding the universal sources of culture through exploring diversity, with a particular focus on the role of Africa as the cradle of humanity and dynamic initiatives on the continent. Through collaborative advocacy and the interdisciplinary approach of Leonardo daVinci (1452-1519), relevant generalities for human rights education and humanitarian efforts, this paper contextualizes intercultural dialogue for universal equity in young people’s development. The paper also explores how education influences the political developments of learners. The paper then shows how humanistic and intercultural approaches to education are fostering creative and critical thinkers worldwide.